Nuevos registros de poblaciones de Corynabutilon ochsenii (Phil.) Kearney a una mayor altitud, en formaciones vegetales post incendio en la Reserva Nacional Malleco, Chile - NEIRA, ZOIA; SAAVEDRA, MARCELO; CALZADILLA, SORAYA; HERNÁNDEZ, MARCELO; OBREQUE, CECILIA (Gayana Botánica, 2012)
We report new records of Corynabutilon ochsenii (Phil.) Kearn ey populations in areas affected by forest fires 12 years ago at the Malleco National Forest Reserve in southern Chile. One of the populations is found at 1350 m a.s.l., which is the highest altitude ever reported for this species. C. ochsenii is part of the species that are reestablishing after the fire.